A case report of rabies in a striped hyena (hyaena hyaena) in fars province of iran - Ehsan SAEIDI; Foozhan KHERADMAND (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2022)
Rabies is an infectious, highly fatal and true zoonotic disease. Disease remains endemic and a major public health problem in Iran. In this article, we describe a case report of rabies in a Striped Hyena (Hyaena hyaena) in Iran. One Striped Hyena was found in Fars Province Near human communities in a landfill site. Clinical signs were characterized by severe states of depression, blindness, ataxia, anorexia, lethargy and tenesmus. Due to clinical signs and suspected rabies, the animal was euthanized. The brain samples were taken from the Hyena and transported fresh on ice to the laboratory of Pasteur Institute of Iran. Fluorescent antibody technique (FAT) confirmed rabies infection in the Striped Hyena.